Combinatorics?

Let S = r = 1 33 ( r 2 3 ) ( 97 3 r 2 ) S = \displaystyle\sum_{r=1}^{33}\left(r-\dfrac{2}{3} \right)\dbinom{97}{3r-2}

Where S = k ( 2 94 + 1 2 ) S = k(2^{94}+\frac{1}{2}) . Find k \lfloor k \rfloor .

Notation : ( M N ) \dbinom MN denotes the binomial coefficient , ( M N ) = M ! N ! ( M N ) ! \dbinom MN = \dfrac{M!}{N!(M-N)!} .


The answer is 43.00.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Sabhrant Sachan
Dec 27, 2016

Starting with Binomial expansion of ( 1 + x ) n (1+x)^n

( 1 + x ) n = ( n 0 ) + ( n 1 ) x 1 + + ( n n ) x n n ( 1 + x ) n 1 = 1 ( n 1 ) + 2 ( n 2 ) x 1 + + n ( n n ) x n 1 1st derivative n 2 n 1 = ( n 1 ) + 2 ( n 2 ) + + n ( n n ) put x=1 n ( 1 + ω ) n = ( n 1 ) + 2 ( n 2 ) ω 2 + + n ( n n ) ω n 1 put x= ω n ( 1 + ω 2 ) n = ( n 1 ) + 2 ( n 2 ) ω 4 + + n ( n n ) ω 2 n 2 put x= ω 2 \begin{aligned} (1+x)^{n} & = \dbinom{n}{0}+\dbinom{n}{1}x^1+\cdots+\dbinom{n}{n}x^n \\ n(1+x)^{n-1} & = 1\dbinom{n}{1}+2\dbinom{n}{2}x^{1}+\cdots+n\dbinom{n}{n}x^{n-1} & \small\color{#3D99F6}{\text{1st derivative}} \\ n\cdot 2^{n-1} & = \dbinom{n}{1}+2\dbinom{n}{2}+\cdots+n\dbinom{n}{n}& \small\color{#3D99F6}{\text{put x=1 }} \\ n(1+\omega)^{n} & = \dbinom{n}{1}+2\dbinom{n}{2}\omega^{2}+\cdots+n\dbinom{n}{n}\omega^{n-1} & \small\color{#3D99F6}{\text{put x= }} \omega \\ n(1+\omega^{2})^{n} & = \dbinom{n}{1}+2\dbinom{n}{2}\omega^{4}+\cdots+n\dbinom{n}{n}\omega^{2n-2} & \small\color{#3D99F6}{\text{put x= }} \omega^{2} \end{aligned}

Add all the three equations

n ( 2 n 1 + ( 1 + ω ) n + ( 1 + ω 2 ) n ) = 3 [ 1 ( n 1 ) + 4 ( n 4 ) + 7 ( n 7 ) + + ] n 3 [ 2 n 1 + 2 cos ( ( n 1 ) π 3 ) ] = 1 ( n 1 ) + 4 ( n 4 ) + 7 ( n 7 ) + 97 3 [ 2 96 + 2 cos ( 96 π 3 ) ] = r = 1 33 ( 3 r 2 ) ( 97 3 r 2 ) 97 3 [ 2 96 + 2 cos ( 96 π 3 ) ] = r = 1 33 ( 3 r 2 ) ( 97 3 r 2 ) 97 3 [ 2 96 + 2 ] = r = 1 33 ( 3 r 2 ) ( 97 3 r 2 ) 4 × 97 9 [ 2 94 + 1 2 ] = r = 1 33 ( r 2 3 ) ( 97 3 r 2 ) k = 388 9 k = 43 \begin{aligned} n\left( 2^{n-1}+(1+\omega)^{n}+(1+\omega^{2})^{n} \right) & = 3\left[ 1\dbinom{n}{1}+4\dbinom{n}{4}+7\dbinom{n}{7}+\cdots+ \right] \\ \frac{n}{3}\left[2^{n-1}+2\cos{\left(\dfrac{(n-1)\pi}{3}\right)}\right] & = 1\dbinom{n}{1}+4\dbinom{n}{4}+7\dbinom{n}{7}+\cdots \\ \frac{97}{3}\left[2^{96}+2\cos{\left(\dfrac{96\pi}{3}\right)}\right] & = \displaystyle\sum_{r=1}^{33}\left(3r-2\right)\dbinom{97}{3r-2} \\ \frac{97}{3}\left[2^{96}+2\cos{\left(\dfrac{96\pi}{3}\right)}\right] & = \displaystyle\sum_{r=1}^{33}\left(3r-2\right)\dbinom{97}{3r-2} \\ \frac{97}{3}\left[ 2^{96}+2 \right] & = \displaystyle\sum_{r=1}^{33}\left(3r-2\right)\dbinom{97}{3r-2} \\ 4\times\frac{97}{9}\left[ 2^{94}+\dfrac{1}{2} \right] & = \displaystyle\sum_{r=1}^{33}\left(r-\frac{2}{3}\right)\dbinom{97}{3r-2} \end{aligned} \\ k = \boxed{\dfrac{388}{9}} \\ \lfloor k \rfloor = 43

Both the brackets look like binomial coefficients.Could you please edit that .Anyways ,Great solution.

DarK MAPHiC - 3 years, 2 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...